2013
DOI: 10.1155/2013/378657
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Therapies for Type 2 Diabetes Mellitus: Chemistry, Biology, and Potential Application of Selected Plants and Compounds

Abstract: Diabetes mellitus has been recognized since antiquity. It currently affects as many as 285 million people worldwide and results in heavy personal and national economic burdens. Considerable progress has been made in orthodox antidiabetic drugs. However, new remedies are still in great demand because of the limited efficacy and undesirable side effects of current orthodox drugs. Nature is an extraordinary source of antidiabetic medicines. To date, more than 1200 flowering plants have been claimed to have antidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
159
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(179 citation statements)
references
References 213 publications
2
159
0
8
Order By: Relevance
“…The plant Galega offcinalis (French lilac or goats rue) is the origin of Metformin which represents the first line in the management of type II diabetes. In the medical literature hundreds of plants have been claimed to be useful for the treatment of diabetes [4]. A recent study of CAM use in people with diabetes demonstrated a huge variation in the prevalence of CAM use across the world from 17% to 73% [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant Galega offcinalis (French lilac or goats rue) is the origin of Metformin which represents the first line in the management of type II diabetes. In the medical literature hundreds of plants have been claimed to be useful for the treatment of diabetes [4]. A recent study of CAM use in people with diabetes demonstrated a huge variation in the prevalence of CAM use across the world from 17% to 73% [5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a high prevalence of diabetes among the Gulf States coupled with a long tradition of CAM use. A recent study in Saudi Arabia revealed a prevalence of CAM use for the management of diabetes of 30% [4]. A recent study of pregnant females in Qatar found the prevalence of CAM use to be 29% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed extracts from Momordica charantia, Tinospora cordifolia, and Zingiber officinale herbal plants to contain alkaloid compounds with α-glucosidase inhibitory properties with hypoglycemic effect on several animal studies and small-scale human studies [18][19][20][21]. Moreover, it has been reported that consumption of M. charantia in raw or juice form can be efficacious in lowering blood glucose levels [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin secretion and resistance, α-glycosidase activity, and in cretin production are the targets of present medicines. Botanicals are complex mixtures of compounds with multiple targets, which makes clinical trials complicated (9).…”
mentioning
confidence: 99%
“…Some botanicals exert their antidiabetic effects via multiple mechanisms; examples of these botanicals are berberine, bitter melon, capsaicin/chili pepper, ginseng, turmeric, mate tea, ginger/gingerol, Chinese tea, soybean, Aloe vera, quercetin, resveratrol, and coffee (9). Thus, the scope of our investigation is finding the exact mechanism of function, molecular targeting, and standardization of herbal formulations besides using well-designed clinical trials (9).…”
mentioning
confidence: 99%